Using iREAD in understanding online reading strategies applied by science and technology students - Ruhil Amal, Azmuddin; Nor Fariza, Mohd Nor; Afendi, Hamat (IGI Global, 2018)
This article describes how with the growth of online learning, reading hypertext materials requires both online reading and navigational strategies. This article was conducted as part of a pilot study on qualitative data collection into reading of Science and Technology hypertexts that focuses on reading and navigational strategies of five university students enrolled in undergraduate Engineering programs. It presents the application of iREAD; Interactive Reading for Academic Disciplines that integrates various e-literacy tools to facilitate reading of academic hypertexts. Student's participation was within iREAD through the use of annotation tool and discussion forum. The two-phased data collection was conducted qualitatively through semi-structured interviews, screen records, and retrospective interviews. The results show that the participants mainly used a global reading strategy, serial, and mixed overview navigational strategies in the online reading environment. In addition, the article concluded that iREAD assists students to understand and organize hypertexts materials better with the use of e-tools.